The Future of the Humanities: Preserving and Transmitting Human Knowledge and Values in the 21st Century - Musyarrafah Sulaiman Kurdi (Social Studies and Humanities Journal (SOSHUM), 2024)
This research investigates the impact of developments in information technology and digitalization on approaches and understanding in the field of humanities in the 21st century. Through a systematic literature review, we explore key concepts in the relationship between information technology and the humanities and analyze the implications of these interactions. The research method involved collecting articles from reputable international databases using relevant keywords, followed by detailed analysis using the PRISMA method. The results of the discussion show that the development of information technology has changed the paradigm in approaches to the humanities, influencing educational practices, analysis and interpretation of humanities works. The implications of this research underscore the importance of integrating information technology with humanities pedagogy and the need for attention to ethics, authenticity, and integrity in the use of technology in humanities contexts.